Pronounced increase in slope instability linked to global warming: A case study from the eastern European Alps - Savi, Sara; Comiti, Francesco; Strecker, Manfred R. (Earth Surface Processes and Landforms, 2021)
In recent decades, slope instability in high-mountain regions has often been linked to increase in temperature and the associated permafrost degradation and/or the increase in frequency/intensity of rainstorm events. In this context we analyzed the spatiotemporal evolution and potential controlling mechanisms of small- to medium-sized mass movements in a high-elevation catchment of the Italian Alps (Sulden/Solda basin). We found that slope-failure events (mostly in the form of rockfalls) have increased since the 2000s, whereas the occurrence of debris flows has increased only since 2010. The current climate-warming trend registered in the study area apparently increases the elevation of rockfall-detachment areas by approximately 300 m, mostly controlled by the combined effects of frost-cracking and permafrost thawing. In contrast, the occurrence of debris flows does not exhibit such an altitudinal shift, as it is primarily driven by extreme precipitation events exceeding the 75th percentile of the intensity-duration rainfall distribution. Potential debris-flow events in this environment may additionally be influenced by the accumulation of unconsolidated debris over time, which is then released during extreme rainfall events. Overall, there is evidence that the upper Sulden/Solda basin (above ca. 2500 m above sea level [a.s.l.]), and especially the areas in the proximity of glaciers, have experienced a significant decrease in slope stability since the 2000s, and that an increase in rockfalls and debris flows during spring and summer can be inferred. Our study thus confirms that "forward-looking" hazard mapping should be undertaken in these increasingly frequented, high-elevation areas of the Alps, as environmental change has elevated the overall hazard level in these regions.